Real exchange rate misalignment and economic growth in Nigeria - Abdulkadir I. Ali; Isaiah O. Ajibola; Babatunde S. Omotosho; Olutope O. Adetoba; Abiola O. Adeleke (CBN Journal of Applied Statistics, 2015)
This paper investigates the impact of Naira real exchange rate misalignment on Nigeria's economic growth using quarterly data spanning the period 2000-2014. We derive estimates of Real Exchange Rate Misalignment (RERMIS) by computing deviations of the actual real exchange rate from a sustainable equilibrium path that is determined using the Behavioural Equilibrium Exchange Rate (BEER) approach of Edwards (1989). Our modelling approach accounts for the possible effects of endogeneity and structural breaks in the estimated relationships. In terms of the extent of RERMIS, results show that the naira was on the average overvalued by 0.17 per cent during the study period. The Gregory and Hansen procedure provides evidence of cointegration between output and its determinants with a structural break in 2003Q2. Furthermore, we found empirical support for a negative impact of RERMIS on economic growth. In view of these findings, the study recommends the continued use of market-based exchange rate arrangements as a way of ensuring that the naira real exchange rate follows its path of sustainable equilibrium. This would complement other government policies aimed at promoting economic growth in the country.
Keywords: O40; F31; 330; Real exchange rate misalignment; Error correction model; Cointegration; Structural break